Placebo responses to antidepressants - Lane, Roger (German Journal of Psychiatry, 1999)
Posted date: 1999. Much has been made of the 'miraculous powers' of placebo. It has even been speculated that antidepressants are little more than sophisticated placebos. However, a distinction should be made between the specific therapeutic response to placebo and the improvement that occurs in a patient who is being treated with placebo. In randomized controlled trials (RCTs) of antidepressants where an 'active' drug treatment is compared against inert placebo pill in patients with affective disorders, such as major depression, neither the patient nor the treating physician knows the treatment that is being administered. In these studies the response to placebo is often at least half of that to drug and is sometimes so high that the response to drug treatment is not statistically significantly greater than that to placebo. This phenomena has been used to infer that antidepressant drug treatments are not particularly effective, and indeed that they may have no intrinsic activity whatsoever. In this article, examples, taken mainly from the extensive database of RCTs for the selective serotonin reuptake inhibitor (SSRI) antidepressant sertraline, are used to provide reassurance as to the efficacy of pharmacotherapy in the treatment of patients with mood and anxiety disorders (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: Affective Disorders; Antidepressant Drugs; Anxiety Disorders; Drug Therapy; Experiment Controls; Placebo; SSRI; Sertraline; antidepressants; anxiety disorder; depression; pharmacotherapy; placebo; randomized controlled trials; sertraline; treatment effectiveness